Fruit development modelling and performance analysis of automatic greenhouse control. (August 2021) - Kuijpers, Wouter J.P.; Antunes, Duarte J.; Hemming, Silke; van Henten, Eldert J.; van de Molengraft, Marinus J.G.
Abstract : This paper presents a receding horizon optimal control (RHOC) method with an economic objective function for balancing the cost of resources ( resource use × cost ) with income through yield ( yield × product price ). This paper considers the two elements that determine the income through yield. The first element is yield and associated fruit development. A new, computationally viable, approach to model the income through yield is proposed and its prediction accuracy with respect to the original model is evaluated. The new approach employs a model that predicts at each time step, the future income through yield based on the assimilates partitioned to the fruits at the current time step. Simulations suggest that the assumptions made to arrive at the model for the new approach, do not significantly affect the accuracy of the predictions. The second element considered in this paper is the product price and the uncertainty inherent in its forecasts. Historical product price data are used to generate artificial product price forecasts. An uncertainty analysis, in combination with the artificial product price forecasts, showed that the product price forecast error does not considerably affect the optimised control strategy. Season-wide simulations with RHOC suggest that the product price forecast error does not considerably affect the value of the economic objective function. Highlights: A computationally viable approach to model the income through yield is proposed. The new approach to model income through yield allows for RHOC with a short horizon. Historical product price data are used to create artificial product price forecasts. Product price forecast errors do not considerably affect the control strategy.